The Implementation of Restorative Justice Principles in Handling Cases of Children in Conflict With the Law - Rasiwan, Iwan; Khoirul Harisin, Miljam; Yaqzhan Kalamul Haq, Muhammad (Fox Justi : Jurnal Ilmu Hukum, 2025)
Children, as the future of a nation, need special attention to ensure they grow into capable and well-rounded individuals. This requires not only proper guidance but also legal support to address any challenges they may face. When children come into conflict with the law, resolving their cases through diversion—using a restorative justice approach—can be a more constructive alternative. This approach focuses on healing and requires the consent of the victim and/or their family, as well as the child’s willingness to participate. This study takes a qualitative approach, gathering data through a literature review using sources from Google Scholar. The research method involves collecting and analyzing relevant written documents. Findings suggest that restorative justice offers a more humane and forward-thinking way to handle juvenile cases. By prioritizing rehabilitation, fostering responsibility, and involving all relevant parties, this method has the potential to create meaningful change for children, victims, and society as a whole.